The Novel Methylation Biomarker SCARA5 Sensitizes Cancer Cells to DNA Damage Chemotherapy Drugs in NSCLC - Peng, Qi; Liu, Yan; Kong, Xuehua; Xian, Jie; Ye, Lin; Yang, Li; Guo, Shuliang; Zhang, Yan; Zhou, Lan; Xiang, Tingxiu (Frontiers in Oncology, 2021)
Background: Scavenger Receptor Class A Member 5 (SCARA5), also known as TESR, is expressed in various tissues and organs and participates in host defense. Recent studies have found SCARA5 to produce an anti-tumor effect for multiple tumors, although the mechanistic basis for the effect is unknown. Methods: Bioinformatics, methylation-specific polymerase chain reaction (MSP), quantitative real-time PCR, and immunohistochemistry were used to assess promoter methylation and expression of SCARA5 in lung cancer tissues and cell lines. The biological effect of SCARA5 on lung cancer cells was confirmed by the CCK8 assay,colony formation assay, and flow cytometry. GSEA,Western blot, RNA sequencing, and luciferase-based gene reporter assay were used to explore the mechanistic basis for the anti-tumor effect of SCARA5. Chemosensitivity assays was used to evaluate the anti-tumor effect of SCARA5 in conjunction with chemotherapeutic drugs. Results: We found SCARA5 to be downregulated in lung cancer cell lines and tissues with SCARA5 levels negatively related to promoter methylation. Ectopic expression of SCARA5 suppressed proliferation of lung cancer both in vitro and in vivo through upregulation of HSPA5 expression, which inhibited FOXM1 expression resulting in G2/M arrest of the A549 cell line. SCARA5 also improved susceptibility of A549 cells to chemotherapeutic drugs that damage DNA. Conclusion:SCARA5 was silenced in NSCLC due to promoter methylation and could be a potential tumor marker in NSCLC.